Digital Marketing Training And Guidance For The Virageawie Disabled Community - Permadi, Dian; Maharani, Sabrina; Marshanda, Shafa Dwi; Jaya, Rama Chandra; Ramdan, Ahmad Taufiq Maulana; Lubis, Ira Aryanti Rasyi; Wiryany, Detya (Inaba of Community Services Journal, 2024)
Training as well as digital marketing guidance has been held for the disability community VirageAwie in Cimareme Village, Ngamprah District, West Bandung Regency. This activity aims to increase knowledge and skills in digital marketing, especially for disability community members. The program starts with FGD to identify problems, then to be continued with VirageAwie.com website creation and training themed Digital Marketing Introducing Business Through Social Media Content. Training covers discussion about marketing through social media, methods photography, videography, and product promotion. Findings show the existence of significant improvement in participants' understanding about digital marketing as well as their ability to use digital platforms to enlarge market reach. A good influence was seen in the increased ability and independent financial sustainability of the participants. This initiative needs more cooperation continued with communities, academics, and government to strengthen network marketing as well as quality power work, so that VirageAwie products can compete in the local to global market.